Pengaruh Kepatuhan Diet Pasien Terhadap Perkembangan Asites Pasien Gagal Ginjal Di Unit Hemodialisis RS Tk. II dr. Soedjono Magelang - Endro Haksara; Ainnur Rahmanti; Margiyati Margiyati; Indah Septiyani Triabadi (Lembaga Pengembangan Kinerja Dosen, 2023)
The patients with chronic kidney failure, if they do not limit their intake of fluids, food and an appropriate daily diet, it will cause malnutrition and accumulation of fluid in parts of the body, including the face, hands and feet. Fluid buildup can also occur in the abdominal area or what is usually called ascites. Ascites is an important problem and often occurs in patients undergoing hemodialysis. Ascites will cause stomach enlargement and excess weight gain. The aim of this study was to determine the effect of patient diet compliance on the development of ascites in kidney failure patients in the hemodialysis unit at Tk Hospital. II dr. Soedjono Magelang. This type of research is descriptive analytic using a cross-sectional method. The sampling technique used the Purposive Sampling method with a sample size of 46 respondents. Statistical analysis uses the chi-square test. The results of this study showed p=0.002, which means there is an influence between diet compliance and the incidence of ascites in the Hospital Hemodialysis Unit. Kindergarten II dr. Soedjono Magelang. The more patient compliance with a nutritional diet will have a better impact on the development of ascites.